2023
DOI: 10.1021/acssuschemeng.2c06683
|View full text |Cite
|
Sign up to set email alerts
|

Turning Recycled Cardboard Container-Derived Lignin-Containing Cellulose Nanofibrils into a Robust Gas Barrier UV-Shielding Film

Abstract: Self-standing cellulose nanofibril (CNF) films are regarded as one of the promising alternatives to current petroleum-based packaging materials mostly due to their ability to form dense self-assembled structures exhibiting high gas barrier properties. Nonetheless, one of the major obstacles to the commercialization of these materials in packaging applications is the high cost of raw materials and production energy. In this study, we created self-standing films of lignin-containing cellulose nanofibrils (LCNFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Additionally, self-standing films made from LCNFs obtained from recycled corrugated cardboard pulp have been shown in experiments to be able to achieve 100% UV-blocking properties. 73 What's more, it was reported that the LCNFs extracted from mechanical pulp have a high lignin content of 26.8% to 38.5%, and the resulting LCNF films exhibit high transparency and strong UV-blocking properties (Fig. 2a).…”
Section: Biodegradable Substratesmentioning
confidence: 96%
“…Additionally, self-standing films made from LCNFs obtained from recycled corrugated cardboard pulp have been shown in experiments to be able to achieve 100% UV-blocking properties. 73 What's more, it was reported that the LCNFs extracted from mechanical pulp have a high lignin content of 26.8% to 38.5%, and the resulting LCNF films exhibit high transparency and strong UV-blocking properties (Fig. 2a).…”
Section: Biodegradable Substratesmentioning
confidence: 96%
“…15 This attention is primarily due to their capacity to create densely self-assembled structures when dried, owing to robust capillary forces, hydrogen bonding, and London dispersion forces. 5,7 This unique quality results in impressive gas barrier properties and mechanical strength. 7 Moreover, CNFs are typically generated through high-shear mechanical disintegration methods involving highpressure homogenizers, grinders, or microfluidizers.…”
Section: Introductionmentioning
confidence: 99%
“…Being the most prevalent natural biopolymer featuring affordability, impressive sustainability, and exceptional biodegradability, , cellulose merits significant consideration. The utilization of this biopolymer as a chemical feedstock began only around 170 years ago with the discovery of the first cellulose derivative (cellulose nitrate) by Braconnot .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations